1993
DOI: 10.1172/jci116588
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dosage progestin-only administration upon plasma triglycerides and lipoprotein metabolism in postmenopausal women.

Abstract: Oral administration to five postmenopausal women of dl-norgestrel (0.075 mg/d for 7 wk) reduced mean fasting plasma levels of triglycerides by 29% (P < 0.001), VLDL triglycerides by 39% (P < 0.01), and VLDL apo B by 26% (P < 0.05), while lowering mean total cholesterol by 7% (P < 0.06). To explain these observations the kinetics of VLDL and LDL apo B turnover were studied by injecting autologous "25I-labeled VLDL and "311-labeled LDL under control conditions and again in the fourth week of a 7-wk course of dl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Wolfe & Huff [45] observed reduced LDL production and LDL apoB pool size without changes in the LDL clearance rate in postmenopausal women treated with combined oral 17-oestradiol and dl-norgestrel. They have also found that progestin administration alone increases LDL apoB production, but this effect is compensated for by a concomitant increase in the fractional catabolic rate of LDL apoB, resulting in an unchanged LDL apoB pool size [46]. Consistent with these previous findings in the transdermal group, no further alterations were observed in the density distribution and composition of LDL during the MPA phase compared with the oestrogenalone phase.…”
Section: Discussionsupporting
confidence: 68%
“…Wolfe & Huff [45] observed reduced LDL production and LDL apoB pool size without changes in the LDL clearance rate in postmenopausal women treated with combined oral 17-oestradiol and dl-norgestrel. They have also found that progestin administration alone increases LDL apoB production, but this effect is compensated for by a concomitant increase in the fractional catabolic rate of LDL apoB, resulting in an unchanged LDL apoB pool size [46]. Consistent with these previous findings in the transdermal group, no further alterations were observed in the density distribution and composition of LDL during the MPA phase compared with the oestrogenalone phase.…”
Section: Discussionsupporting
confidence: 68%
“…In one, progestin had no effect on the efficiency of VLDL-apoB-100 removal in postmenopausal women (60). In another, cross-sectional study, oral contraceptives, containing progestins only or estrogens plus progestins, were associated with higher endogenous and exogenous TG removal from plasma compared with no treatment or estrogens alone (28).…”
Section: Discussionmentioning
confidence: 96%
“…15 and 48). Oral estrogen administration increases VLDL-TG and VLDL-apoB-100 secretion and concentration in plasma (9,15,48), whereas oral administration of progestins elicits the opposite effect and lowers VLDL-TG and VLDL-apoB-100 concentrations and VLDL-apoB-100 secretion (15,48,60), although it apparently has no effect on VLDL-TG secretion (28). The difference between these findings and ours may be due to differences in the amount of sex hormones available: exogenous hormone administration in the earlier published studies resulted in relatively high, steady hormone concentrations in the systemic circulation that were maintained for several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, estrogen administration in rats reduces the expression of the HDL receptor, scavenger receptor class B type I (SR‐B1) on liver cells (for a review see Ref [42]). In contrast to estrogens, androgens are known to inhibit the VLDL triglyceride synthesis [20, 21], whereas they increase HL activity [23, 24] and consequently lower HDL cholesterol levels [22, 43].…”
Section: Discussionmentioning
confidence: 99%
“…VLDL metabolism is strongly in¯uenced by estrogens and androgens, the former enhancing the VLDL triglyceride synthesis in the liver [18,19] and the latter decreasing it [20,21]. Estrogens inhibit hepatic lipase (HL) activity [22,23], whereas androgens have a stimulating effect [23,24].…”
Section: Introductionmentioning
confidence: 99%